With the wind and the waves: a guide to mental health practices in Alaska Native communities - Droby, Ray M., author; University of Alaska Press, publisher (Colorado State University. Libraries, 2020)
The following model for mental health professionals working within Alaska Native communities maintains four guiding principles fueling its infrastructure. Embodied within its framework is its particular emphasis on non-Native practitioners working alongside village-based personnel coupled with the need to understand and accept Native people for who they are, working with them on an individual and community level. Following my experience on the ocean with the wind and the waves, it recognizes and emphasizes mental health professionals going with what is given in a Native community. Further, although my reference to "mental health professionals" is often intended for non-Native mental health providers, this does not exclude Native mental health providers due to these reasons: 1) some American Indian providers who move to Alaska to practice in rural/remote Alaska villages are not familiar with Alaska Native culture or the history of trauma experienced by Alaska Native people; 2) for a variety of reasons (e.g., raised outside of Alaska and not connected to the culture), some Alaska Native providers may not be familiar with their culture or history; this is not uncommon since most of the Alaska Native history is not taught in school but rather through Elders and the practice of oral tradition.--Provided by publisher.
One. With the Wind and the Waves: A Guide for Mental Health Practices in Alaska Native Communities -- Two. Guiding Principles for Mental Health Professionals Working in Alaska Native Communities -- 1. Self-Determination Is an Inalienable Right for Alaska Natives -- 2. Native Self-Determination Is Best Promoted Through Decentralized Mental Health Services -- 3. The Role of the Mental Health Professional Imparts a Co-Participatory and Background Presence -- 4. The Role of the Mental Health Professional Is Multifaceted and Collectively Mindful -- Three. Cultural Considerations When Working in Alaska Native Communities -- Mindset, Transference Issues, and the Strengths of Alaska Native Communities -- Collective Colonizing Trauma and Specific Traumas on Native Communities -- Culture of Silence -- Collectivism -- Four. Therapy Considerations -- Relational-Cultural Theory -- Relational-Cultural Therapy and Multicultural Care -- Psychotherapy with Alaska Natives -- Case Examples of the 4Rs with Alaska Natives -- Initial Treatment Engagement -- Parenting and the Use of Parent-Child Interaction Therapy (PCIT) -- Strengths Perspective -- Trauma-Focused Narrative Therapy with Children -- Crisis Intervention -- Psychotropic Medication -- Bibliotherapy -- Five. Adjunctive Considerations -- Self-Determination Versus Dependency -- Dependency Patterns -- Colonization Patterns -- Indigenous Community-Based Approaches to Solving Problems -- Tribal Problems, Tribal Solutions -- Personal Biases/Worldview -- Generalist Orientation -- Hurting Helpers -- Personal Well-Being (PWB) -- Native Spirituality -- Native Identity -- The Assets Study -- Flow -- Tribal Healers -- Learning and Communication Styles -- Maslow's Hierarchy of Needs -- Trust/Mistrust -- Working with Schools in Alaska Native Communities -- Ethics -- Psychological Testing and Alaska Natives -- Psychiatric Disorders, ACEs, Epigenetics, and Alaska Natives -- Working with "Resistance" and Stages of Change, Community Readiness, and Healing -- Self-Care -- Six. Prevention Considerations -- Seven. Concluding Thoughts.
Keywords: Alaska Natives -- Mental health services; Psychiatry, Transcultural -- Alaska; Mental health services